Physical Exercises By Giving Glutathione for Changes of Leukocytes, Neutrophils, and Lymphocytes Amounts - Yanuarti, Tuty; Sugiharto, Sugiharto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2020)
Physical exercise changes the antibody endurance of each person. This study aims to determine in depth changes in the number of leukocytes, neutrophils, and lymphocytes using physical exercise after being given glutathione. The method used experimentally using a posttest randomized control group design. The study was conducted in three groups where each group consisting of men and women who are in the age range of 20-30 years. Each group consisted of 10 people (n), K1 was given a placebo, K2 was given glutathione 54 mg / kg BW, K3 given 108 mg / kg BW. All treatments are given intraperitoneally twice a day until the third day. Maximum physical exercise is swimming. On the third day after 3 hours of treatment (placebo or glutathione), then participants take a leukocyte profile measurement. The findings show that the number of leukocytes: K2> K1; P = 0.005; K2 - K3; P = 0.168; - K3; P 0.105, neutrophils: Kl, K2 and K3 are not different, even though K2 is highest, lymphocyte: K2> K1; P = 0.003, K1 - K3 and K2 - K3 is not different even though K2 is highest. The conclusion of this study is the number of leukocytes and lymphocytes treated with glutathione 54 mg / kg BW (K2) is significantly higher than K1 after strenuous physical exercise. Thus, the content of glutathione must be balanced with the body’s needs so that the body is healthy and is able to do the heavy activities.